Condition optimization of sea pandan leaves biosorben synthesis and adsorptivity test on chromium and lead metal ions in different kinds of waste - Susila Kristianingrum; Endang Dwi Siswani; Annisa Fillaeli (Jurnal Sains Dasar, 2014)
This study aims to determine whether or not biosorben synthesized from sea pandanus leaves, the influence of the type of acid used, the optimum adsorption efficiency of Cr and Pb metal ions from various wastes, as well as the synthesis results of biosorben character. The subjects were biosorben of sea pandanus Pandanus tectorius types of Java's southern coast. The objects are adsorptive properties and the character of the pandanus sea biosorben synthesized before and after activation. Purposive sampling is used as the sampling technique. The independent variables are the type of activator (HCl and H2SO4) and waste water. The dependent variables are the adsorptive nature and character of the sea pandanus biosorben synthesis results. The study was conducted in three phases, namely the manufacture of biosorben sea pandan leaves, characterization and determination of adsorption efficiency (Ep) biosorben synthesized on metal ions of Cr and Pb in batik waste, leachate, and oil. Qualitative and quantitative analysis are done using Atomic Absorption Spectrophotometer instrument at a wavelength of 357.9 nm for Cr and 217 nm for Pb. Biosorben characterization was conducted on the moisture content, ash content, volatile content, and carbon content compared with SNI 06-3730-1995 and analyzed by FTIR spectra. It is also seen biosorben surface area of synthesized both before and after activation by porosimetry. Biosorben of pandanus sea has to be synthesized. Biosorben synthesized with 5% H2SO4 solution produced optimum Ep for Cr and Pb metal ions from waste leachate obtained are 75.831% and 98.714%. Character biosorben activation results in a solution of 5% HCl and H2SO4 by FTIR have almost similar spectra. Moisture content, ash content, volatile content, and carbon content of biosorben synthesized with 5% HCl and 5% H2SO4 in accordance with SNI 06-3730-1995. Porosimetry characterization of biosorben synthesized before activation is 3.5756 m2 / g, whereas after activation with HCl 5% to 770.7636 m2/g, and after activation with 5% H2SO4 solution become 153.7002 m2/g. Keywords: biosorben, sea pandanus, adsorptivity test, chromium, lead